Development of a Multimedia Program to Promote Environmental Education of Zoology - Valladares Fuente, Fernando Emilio (Society & Sustainability, 2020)
The purpose of this study was to improve the approach of environmental education in a secondary school in Pinar del Río, Cuba. This material was created using a) literature on the theoretical?empirical background of environmental education focused on Zoology and b) a study of student perceptions of the environment using surveys and interviews. Deficiencies noted in the literature and student knowledge guided the design of a multimedia program to teach Zoology to high school students with a focus on an integrated environmental approach. The proposed program includes specialized videos and texts about both global and local fauna. The videos and activities were designed to familiarize students with the fauna and the measures that they should take to protect and help preserve the life of animals and their environments.